The Contribution of Glacial Isostatic Adjustment to Past and Contemporary Relative Sea-Level Rise Along the Atlantic Coast of Europe - Chapman, Geoffrey Alan (Université d'Ottawa / University of Ottawa, 2024)
Contemporary and future relative sea-level (RSL) rise that can be attributed to anthropogenic climate change sees significant spatial variability as a result of the processes that underlie it. Some of the processes that contribute to RSL rise unrelated to anthropogenic climate change can and have had significant contributions. In this work, we examined the contributions of one of these processes, glacial isostatic adjustment (GIA), in the coastal regions of Atlantic Europe. These regions have seen significant RSL rise associated with a collapsing peripheral bulge throughout the Holocene and are expected to see more throughout the Anthropocene. Using the recently published paleo sea level database (García-Artola et al., 2018) which follows the HOLSEA RSL data assessment and reporting protocol (Khan et al., 2019) we determined optimal Earth model parameters for much of Atlantic Europe. These optimal parameters fit the data well and largely agree with values determined for previous works on peripheral bulges along the coasts of North America. We further used these results to perform a rudimentary sea-level budget analysis at 10 tide gauge stations, yielding results with high uncertainties and significant discrepancies between observed and projected rates of RSL change for half (5) of the tide gauge stations. Our results lead to the conclusion that GIA remains an important factor when predicting present and future RSL change.
Keywords: Sea level changes; Glacial isostatic adjustment (GIA); Vertical Land Motion; Atlantic coast of Europe; Optimal Earth model parameter sets; Tide gauge